Exploring visual search performance in preschool children with Cerebral Visual Impairment: A modified approach. - Hokken, Marinke J; Verboom, Silke; Geldof, Christiaan JA; Escudero, Paola; Kooiker, Marlou JG; Pel, Johan JM (British Journal of Visual Impairment, 2026)
Visual search difficulties are common in children with cerebral visual impairment (CVI), due to higher-order visual selective attention (VSA) deficits. However, little is known about children with CVI below 6 years. This international multi-centre study explored VSA through search performance and efficiency in preschool children aged 3–5 years with CVI (n = 24), or a CVI-risk (n = 20) compared with neurotypical children (n = 47). Search performance on the paper–pencil NEPSY Visual Attention task was measured by accuracy, commission errors, and completion time. Search efficiency was assessed by reconstructing the cancellation path to obtain inter-target distances, intersections, and cluster visits. Children with CVI demonstrated significantly lower accuracy, longer completion times, greater inter-target distances, and more revisits to clusters of targets compared with both CVI-risk and neurotypical children. We conclude that by using a modified approach of a paper–pencil search task, first signs of global and local VSA deficits can be detected, offering clinical insights.